Hantaviruses as emergent zoonoses - Ullmann, L. S. [UNESP]; Souza, L. C. [UNESP]; Langoni, H. [UNESP] (FapUNIFESP (SciELO), 2008)
Hantaviruses belong to the Bunyaviridae family, which consists of vector-borne viruses. These viruses can provoke two infection types: hemorrhagic fever with renal syndrome (HFRS) - which occurs in the Old World-and hantavirus cardiopulmonary syndrome (HCPS) - an emergent zoonosis that can be found in many countries of the western hemisphere. Rodents are hantavirus reservoirs and each species seems to host a different virus type. Humans acquire the infection by inhaling contaminated aerosol particles eliminated by infected animals. The factors involved in the emergence of hantavirus infections in the human population include ecological modifications and changes in human activities. The most important risk factor is contact between man and rodents, as a result of agricultural, forestry or military activities. Rodent control remains the primary strategy for preventing hantavirus diseases, including via health education and hygienic habits.
Keywords: Control; Hantaviruses; Public health; Rodents